Study of Female undergraduate students enrolled in e- learning courses at Taibah University (college of education) and their attitudes towards learning platforms and mobile learning: Edmodo and Blackboard - Aljermawi, Hanan Nassar (Journal of Educational and Psychological Sciences, 2022)
The aim of the current study is to determine the extent to which the female students at the College of Education registered for e- learning courses at Taibah University using educational platforms and their attitudes towards platforms and mobile learning (Edmodo Blackboard as a model). The sample consists of (14) students and two different questionnaires were designed and applied.The first questionnaire consisted of (12) items and related to the students’ use of the Edmodo- Ed platform, and the Bb- Blackboard platform, whereas the second questionnaire consisted of (45) distributed items. The research concluded that the students use the (Ed) platform with a medium degree, and with a mean of (1.96 out of 3), while they use the (Bb) platform with a degree of High, with an arithmetic mean (2.64 out of 3). The results also revealed that the general average of the female students’ attitudes towards the (Ed) platform was (2.52), with a high degree of appreciation, and the arithmetic averages of the female students’ attitudes on the axes of the questionnaire ranged between (2.88- 2.21), with a large to medium degree, while the results revealed that the average the year of the students' attitudes towards the (Bb) platform was (2.53), with a high degree of appreciation, and the arithmetic averages of the students' attitudes on the questionnaire axes ranged between (2.92- 2.25), and to a large to medium degree. The researcher recommended a number of recommendations, including the integration of more than one platform in education and training students on the optimal use of the skills of using educational platforms.
Keywords: Educational platforms; Edmodo; Blackboard; attitudes; Taibah University